2021
DOI: 10.1121/10.0003332
|View full text |Cite
|
Sign up to set email alerts
|

Analysing spectral changes over time to identify articulatory impairments in dysarthria

Abstract: Identifying characteristics of articulatory impairment in speech motor disorders is complicated due to the timeconsuming nature of kinematic measures. The goal is to explore whether analysing the acoustic signal in terms of total squared changes of Mel-Frequency Cepstral Coefficients (TSC_MFCC) and its pattern over time provides sufficient spectral information to distinguish mild and moderate dysarthric French speakers with Amyotrophic Lateral Sclerosis (ALS) and Parkinson's Disease (PD) from each other and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In their study, speed was calculated based on the mean slope of the second formant, which may not be linearly related to actual articulatory speed and may explain discrepancies between our findings for speed and theirs. It may also explain why another acoustic study showed events in the spatial domain to be more sensitive than durational measures in differentiating mild ALS and PD [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, speed was calculated based on the mean slope of the second formant, which may not be linearly related to actual articulatory speed and may explain discrepancies between our findings for speed and theirs. It may also explain why another acoustic study showed events in the spatial domain to be more sensitive than durational measures in differentiating mild ALS and PD [ 45 ].…”
Section: Discussionmentioning
confidence: 99%